Unknown parentage and the challenges of integration into society - Allane, Ahmed; Mechta, Yassine (The International tax journal, 2025)
This article aims to explore the most significant challenges facing individuals of unknown parentage in integrating into society during their various stages of life, beginning with childhood, then adolescence, and finally youth. Each stage has distinct characteristics and features that differ from the previous one. For individuals of unknown parentage, childhood is characterized by the loss of support and the family environment, which is essential for the individual, creating an atmosphere of psychological and social turmoil. This is because the family is distorted for the child of unknown parentage, which reduces the possibility of his smooth integration into society. In addition, the second challenge is represented by the school, which is considered the second environment in which the child of unknown parentage interacts with an environment he has not known before, and what it carries of obstacles that affect, in one way or another, the process of social integration for this group in addition to the social stigma that follows children of unknown parentage at all stages of their life and the devastating social effects that result from it, which limits the integration of children of unknown parentage into society,,,